Etika Talmud Babylonia terhadap Non-Yahudi - Agus Yasin; Ahmad Faizin Soleh (Journal on Education, 2023)
Talmud is the primary cripture of Jewish, and majority of Jewish take Talmud as way of life than torah as second scripture of Jewish. Talmud has devide two parts; Jerussalem and Babylonian Talmud. But now, majority of Jewish use Babylonian Talmud because it was more complete and easier to understand. The teachings on Talmud have teached about ethics in social life, civil right, politics, and criminal laws. But these teachings are very disadvantageous for non-Jewish. And also the teachings have denied ten commandement in the torah as the sripture. Therefore, based on the teaching of Ethics on Babylonian Talmud toward non-Jewish, the writer want to discuss what is the basic foundation of ethical verses on Babylonian Talmud, and the impact and the influence of those teachings. And so the teaching which is dangerous for non-Jewish have coused damage and violence in the life of non-Jewish and life in the world. And the damage and the violence which ware made Israel, come from the teaching on Babylonian Talmud and the teaching of ethics in cosial life, civil right, politics, and criminal laws have already been applied in their daily activities right now. This is the underlying reason for non-Jewish and jewish who hold in torah (antisemitism) to ignore the existence and cannot recognized as scripture. This study uses a descriptive qualitative research method with a data analysis approach from the main sources and books related to the Talmud and its teachings. Through this writing, the author finds a conflict between the teachings in the Talmud and the 10 commandments that have been taught in the Torah, and the formation of ethics in each of these teachings.